Thoracic Sarcoma: A New Glance at the Epidemiological Characteristics of Disease in Iran from 2009 to 2014 - Hamide Rahmani Seraji; Mohmmad Esmaeil Akbari; Hamid Rezvani; Davood Bashash; Maryam Mabani; Atieh Akbari; Alireza Raeisi; Ghasem Janbabee; Sina Salari (Iranian Journal of Public Health, 2022)
Background: The heterogeneity, high rate of mortality and lack of comprehensive diagnostic methods have categorized primary sarcomas of the thorax as a malignancy with dismal outcomes and unknown etiology. Given the fundamental role of epidemiological analysis in establishing management strategies, we designed a study with focus on the epidemiological characteristics of primary thoracic sarcomas in Iran.